PENGARUH INDEPENDENSI AUDITOR, ETIKA AUDITOR, DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT - Rahayu, Titin; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research studies about the influence of independency, ethic, and experience to the audit quality. The scope of this research is all public accountants who work at Public Accountant Firm (KAP) in Surabaya city. The purpose of this research is to analyze the influence of independency, ethic, and auditor experience to the audit quality.This research is a causative research. This research has been done by using hypothesis test and research planning in the form of survey, the samples are 8 KAP in Surabaya and the data applies questionaire which is issued to the Public Accountant Firm(KAP). The research analysis model has been done by using multiple linear regressions.The result of this research shows that independency has significant and positive influence to the audit quality, it shows that the audit quality can be achieved if the the auditorhas independency attitude. Ethic has significant and positive influence to the audit quality, It shows when the auditor ethic is getting better, the audit quality will be better as well. Experience has significant and positive influence to the audit quality, when the length of the work experience which is owned by the auditors is getting better, the audit quality is getting better as well.Keywords: Auditor Independency, Auditor Ethic, Auditor Experience, Audit Quality.